Media Pembelajaran Buku Tematik Berbasis Website - Nurfadillah, Nurfadillah; Wafiah, Andi (Jurnal Sintaks Logika, 2024)
Thematic books are limited, and students cannot repeat learning at home, causing their' understanding of the lessons to be lacking. The aim of this research is to create learning media sourced from thematic books to make the learning process easier for students. This research uses quantitative methods based on a literature study using JavaScript, and XAMPP. The research results show that thematic books as learning media sourced from books that have been modified into website-based applications can be accessed by all students.